An Integrated Imaging Probe Design: The Synthesis of 99mTc/Re‐Containing Macrocyclic Peptide Scaffolds. Issue 2 (11th November 2014) - Hickey, Jennifer L.; Simpson, Emily J.; Hou, Jinqiang; Luyt, Leonard G.
Abstract β‐Sheets account for over 30 % of all secondary structural conformations found in proteins. The intramolecular hydrogen bonding that exists between the two peptide strands is imperative in maintaining this secondary structure. With the proper design, cyclic peptides may act as scaffolds emulating active β‐sheet regions, enabling investigation of their importance in molecular recognition and protein aggregation. Starting from Fmoc‐Lys(Fmoc)‐OH, macrocyclic peptides were synthesized on a solid support, with peptide‐chain elongation extending from both the alpha and epsilon amines of the lysine. The branching peptides were cyclized with a pyridyl tridentate chelation core followed by coordination using [99mTc/Re(CO)3(H2O)3]+. Variable temperature 1H NMR spectroscopy studies were performed, demonstrating that intramolecular hydrogen bonding exists between the two sides of the uncoordinated macrocyclic peptide scaffolds. Additionally, computational modelling and circular dichroism spectroscopic analysis revealed that the peptide backbone exists in a similar conformation both before and after metal coordination. The ability to seamlessly incorporate a tridentate chelation core into the backbone of a macrocyclic peptide, without disrupting the secondary structure, can greatly assist in the design of metal‐centric peptidomimetic imaging agents. This novel integrated imaging probe approach may facilitate the investigation into protein–protein interactions using macrocyclic β‐sheet scaffolds.